Evaluation of internet addiction and fear of missing out among nursing students - Kargin, Maral; Turkben Polat, Hilal; Coskun Simsek, Didem (Wiley, 2020)
Purpose This study was conducted to evaluate the internet addiction and fear of missing out (FoMO) among nursing students. Design and Methods This descriptive study was conducted with 511 nursing students who consent to participate. Results It was found that 3.8% (14 students) of the students participating in the research were pathological internet users. There was a positive correlation between internet addiction and FoMO (r = .332; P = .000). Practice Implications The finding that addiction increases with the increase in the use of social media show us that the excessive use of social media is another risk that threatens the mental health of persons.
Keywords: FoMO; internet addiction; nursing students; social media; nursing students